Zero to maker : learn (just enough) to make (just about) anything - Lang, David, (Inventor), ....-; Demarest, Rebecca, ....- (Sebastopol : Maker Media, 2013)
Are you possessed by the urge to invent, design, and make something that others enjoy, but don't know how to plug into the Maker movement? In this book, you'll follow author David Lang's headfirst dive into the Maker world and how he grew to be a successful entrepreneur. You'll discover how to navigate this new community, and find the best resources for learning the tools and skills you need to be a dynamic maker in your own right. Lang reveals how he became a pro maker after losing his job, and how the experience helped him start OpenROV--a DIY community and product line focused on open source undersea exploration. It all happened once he became an active member of the Maker culture. Ready to take the plunge into the next Industrial Revolution? This guide provides a clear and inspiring roadmap.
Down the rabbit hole -- DIT (do-it-together) -- The maker mentality -- Access to tools -- Craftsmanship -- Digital fabrication -- One to one thousand -- Makers going pro -- Making more makers.
"From Make: magazine"--Cover.
"Make: makezine.com"--Back cover.
Includes index.
Keywords: Technology; Do-it-yourself products industry; Inventors -- Anecdotes; Technologists -- Anecdotes; Businesspeople -- Anecdotes